Hipertermia electromagnética, una alternativa para el tratamiento del cáncer: antecedentes, aspectos físicos y biológicos - Vera Hernández, Arturo; Chong Quero, Jesús Enrique; Leija Salas, Lorenzo; Hernández Mier, Yahir; Marchal, Christian (Revista Mexicana de Ingenieria Biomedica, 2001)
This paper presents a historical review of electromagnetic hyperthermia as well as the biological and physical principles of the technique. This therapy is defined as a temperature rising in tumors to cause lethal effects on them, and it is used as an adjuvant treatment of radio and chemotherapy since it can potentialize lethal effects on cancerous cells. At the end of this paper, we present the future trends of this therapy.